Response of Dry Bean to Sulfentrazone Plus Imazethapyr - Nader Soltani; Christy Shropshire; Peter H. Sikkema (International Journal of Agronomy)
Field studies were conducted in 2010 and 2011 at the Huron Research Station, Exeter, Ontario and from 2009 to 2011 at the University of Guelph Ridgetown Campus, Ridgetown, Ontario to evaluate the sensitivity of four market classes of dry bean to sulfentrazone applied preemergence at 105, 140, and 280 g ai/ha alone and in combination with imazethapyr at 37.5 g ai/ha. At 1 week after emergence (WAE), sulfentrazone alone or in combination with imazethapyr at all doses evaluated caused no significant visible injury in dry bean. At 2 WAE, sulfentrazone alone caused 1–11, 1–11, 1–5, and 3–19% visible injury, and sulfentrazone + imazethapyr caused 3–11, 2–10, 2–5, and 4–20% visible injury in black, cranberry, kidney, and white bean, respectively. At 4 WAE, sulfentrazone alone caused 1–7, 1–7, 0–4, and 1–16% visible injury and sulfentrazone + imazethapyr caused 1–8, 1–5, 1–3, and 2–14% visible injury in black, cranberry, kidney, and white bean, respectively. Sulfentrazone PRE caused slightly greater injury in black and white bean compared to cranberry and kidney bean. Generally, crop injury with sulfentrazone at rates up to 140 g ai/ha alone and in combination with imazethapyr at 37.5 g ai/ha was minimal with no adverse effect on plant height, shoot dry weight, seed moisture content, and yield. Based on these results, there is potential for preemergence application of sulfentrazone at rates up to 140 g ai/ha alone or in combination with imazethapyr at 37.5 g ai/ha in black, cranberry, kidney and white bean.